O uso do Pretérito Imperfeito e do Pretérito Perfeito do Indicativo em português europeu por estudantes com cantonês como L1 - Oliveira, Fátima (2019)
This work aims to verify what conditions of use imply more deviations from the use of Pretérito Perfeito Simples (PPS) and Pretérito Imperfeito (PI) by 21 Chinese learners of Portuguese, A2 level (QECRL), with Cantonese L1, and tries to find some explanations for its occurrence. The quantitative and qualitative analysis is based on the contrast between Portuguese and Cantonese in terms of tense and aspect and describes the most frequent deviations in a corpus of students' written productions. In face of some unexpected results, an analysis of the occurrences in which the Present occurs instead of the expected PPS and the PI was also performed, as a way of confirming or not, possible explanations. The results indicate that there does not appear to be a direct transfer of the value of the perfect and imperfect aspect markers of Cantonese to the use of PPS and PI or the Present, but a transfer of the perfect / imperfect conceptualization in Cantonese, regardless of the tense.